2009
DOI: 10.1093/gerona/glp187
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Microparticles and Procoagulant Activity in Elderly Patients

Abstract: Elderly patients expressed a different pattern of MP in stable conditions, with a different response to sepsis in procoagulant activity modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 44 publications
2
28
2
3
Order By: Relevance
“…Interestingly, angiotensin II may up-regulate the generation of pro-coagulant MPs by human mononuclear cells that confirms a hypothesis about linking between the renin-angiotensin systems to thrombosis [45]. Therefore, there is evidence that elderly persons compared with young persons may have different patterns of expression of mononuclear cells derived MPs and pro-coagulant activity in stable condition and diseases [46].…”
Section: Biological Role and Function Of Mpssupporting
confidence: 59%
“…Interestingly, angiotensin II may up-regulate the generation of pro-coagulant MPs by human mononuclear cells that confirms a hypothesis about linking between the renin-angiotensin systems to thrombosis [45]. Therefore, there is evidence that elderly persons compared with young persons may have different patterns of expression of mononuclear cells derived MPs and pro-coagulant activity in stable condition and diseases [46].…”
Section: Biological Role and Function Of Mpssupporting
confidence: 59%
“…31 Conversely, Forest et al reported that endothelial MPs decrease in individuals aged 75 years and older. 32 Each of these studies involved in vivo measurement of plasma MP levels, where MP clearance may be a significant determinant of concentration. As aging is known to impair clearance of apoptotic cells, 33 we examined MP formation in vitro using a model of endothelial senescence through long-term culture as previously detailed.…”
Section: Discussionmentioning
confidence: 99%
“…The present results contrast, however, with those of Forest et al . [15] The latter authors reported healthy elderly subjects to produce fewer endothelial MVs. It may be that minor, undetected illnesses, influence the production of MVs.…”
Section: Discussionmentioning
confidence: 99%